Effect of test configurations and loading protocols on performance of timber-concrete connectors. (27th February 2023) - Ling, Zhibin; Li, Zhoujun; Rong, Xiuqiang; Shi, Huiyuan
Highlights: Push-out tests were performed on timber-concrete composite (TCC) shear connections with glued-in rod (GIR). Most of the TCC shear connections with GIR mainly failed by the double-hinge yield mode of GIR. Both the test configurations and loading rates showed influence on the shear performance of TCC shear connectors. Calculation modes for shear capacity and shear stiffness were proposed according to typical failure modes of specimens. Abstract: To examine the effect of test configurations and loading protocols on the performance of timber-concrete composite (TCC) shear connectors, a total of twenty-seven TCC shear connections with glued – in threaded steel rod (GIR) were designed to experience push-out tests. The experimental variables include rod diameter, test configurations (single - and double - shear), and loading protocols including the loading protocol (EN26891) and the displacement rate (0.5 mm/min, 2 mm/min, and 4 mm/min). The results indicate that both the test configurations and the displacement rates showed different influences on the performance of the shear connections. Most of the tested TCC shear connections with GIR mainly failed by the double – hinge yield mode of GIR. Double – shear specimens with 16 mm – diameter GIR exhibited a 49 % higher maximum load compared to the single – shear specimens. The slip modulus of the specimens tested at a displacement rate of 4 mm/min was about 40 % lower than that of the specimens tested at the displacement rates of 0.5 mm/min and 2 mm/min, respectively. Among the single-shear specimens, the 16 mm– diameter GIR showed the lowest ductility, by 65 % and 59 %, as compared to the 10 mm – and 12 mm – diameter specimens. Finally, theoretical analytical formulas were proposed to predict the load carrying capacity and the slip modulus of the TCC shear connections with GIR. The experimental slip modulus was also compared with the results obtained by existing calculation models.